Differential Diagnosis of Aamvata and Sandhivata: - A Critical Review - Choudhary, Sangita; Gupta, Nisha (International Research Journal of Ayurveda & Yoga, 2021)
Ayurveda is recognized as the foremost life science and describes multiple ways disease to manifest and manage various disorders. Ayurveda’s holistic approach, treating the diseased holistically, which means targeted interventions for complete physical, psychological and spiritual well-being, makes this science a complete holistic approach in the management of all types of disorders. In today’s era, 1 out of every 5 people suffered from joint pain and swelling. Two major diseases of the joints have been described in Ayurveda as Amavata and Sandhivata. The most common of these diseases affecting the elderly live population are Amavata. The word Amavata is derived from two words "Ama" and "Vata", the word Ama is the condition in which various diseases in the system cause toxic effects. When Ama together with Vata Dosha occupy the mucous place (Astisandhi) then the painful disease "Amavata" occurs. The second common disease Sandhi Vata is a type of Vata-vyadi. This is the most common form of articular disorder. Which can be co-related with Osteoarthritis In today’s modern era, sedentary lifestyle, air conditioned environment in work places, lack of proper healthy diet, travel and old age etc lead to this disease which is increasing day by day. In Sandhivata main symptoms are joint pain and swelling. However, being a physician, it is important to know the etiopathology of each symptom in detail because the pain varies in intensity from case to case and also because treatment protocols vary greatly.Hence its differential diagnosis along with the similar symptoms of various diseases is very important. This article is focusing on the same.